Analisis Komentar Netizen terhadap Kritik Dai TikTok Kepada Dai Televisi - Danasty Naesyah Wandina; Abdul Basit (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2025)
This research was conducted to analyze netizens' comments on the criticism made by Ustadz Rizqi Asfianudin (a TikTok preacher) towards Ning Umi Laila, who discussed the proper way to perform ablution on the RCTI television station's program